Enseñanza de la técnica del pase en las clases de educación física de fútbol en los niños de diez años de edad. Propuesta de una guía metodológica - Grefa Alvarado, Moisés Javier (2016)
The present research has as general objective. Elaborate a methodological guide for the teaching of the passing technique in soccer to the children of ten years of age who receive Physical Education classes belonging to the Basic Bilingual Intercultural Community Educational Center Yawary, Archidona canton, and Napo province. And its central problem; What are the theoretical and methodological foundations for the teaching of pass technique in Physical Education classes in a group of children subject to the investigation, Canton Archidona, Napo province, for? Theoretical methods such as analysis-synthesis, induction-deduction, hypothetico-deductive, among empirical methods, are observation, surveys, review of documents and description, the population was composed of 25 children and 15 docents. The techniques and instruments were; Surveys, questionnaires, and tests. The results reveal the feasibility of the proposal, manifested in the positive changes in the dimension studied as a scientific product designed. I conclude by demonstrating the methodological guide supported in the teaching of the pass technique in the Physical Education class of football in children of ten years of age, will allow it to specify the determinant errors that contribute to improve and individualize the teaching process, conditioning the Gradual increase of the technical skill of the pass.